Peran Perpustakaan dalam Menumbuhkan Literasi Informasi Bagi Anak Tunanetra di Sekolah Luar Biasa Mandailing Natal - Siti Masitoh; Sori Monang; Yusniah Yusniah (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
The purpose of this study was to determine the role of the library in fostering information literacy skills for blind children at the Mandailing Natal Special School (SLB). This study used descriptive qualitative method. The information in this study is the coconut of the Mandailing Natal SLB library. Techniques for collecting data in this study used observation, interviews, and documentation. The results of this study indicate that the role of the library in fostering information literacy must have a special room that is clean and comfortable, arranges the best possible sitting settings. Conduct programs on a schedule, work closely with teachers in using existing resources in the school library. The library at the school is very important, the books available at this time are sufficient, and can help meet the needs of students. Factors that become obstacles to the management of the Mandailing Natal Special School Library (SLB) in fostering information literacy for blind students are the lack of student motivation, human resources, and infrastructure.